2011
DOI: 10.1007/s12519-011-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of menthol in treatment of candidial napkin dermatitis

Abstract: Topical application of menthol may be effective in treatment of candidial ND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Thirteen studies met inclusion/exclusion criteria and are summarized in Table 1. [6][7][8][9][10][11][12][13][14][15][16][17][18] The efficacy of terpenoid-based agents was evaluated for various dermatologic conditions, such as actinic keratosis, 6-10 nonmelanoma skin cancers, 16,18 cutaneous candidiasis, 15 hyperpigmentation, 11 photoaging, 12,14,17 and wounds. 13 Most included studies compared terpenoid-based therapy with vehicle control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies met inclusion/exclusion criteria and are summarized in Table 1. [6][7][8][9][10][11][12][13][14][15][16][17][18] The efficacy of terpenoid-based agents was evaluated for various dermatologic conditions, such as actinic keratosis, 6-10 nonmelanoma skin cancers, 16,18 cutaneous candidiasis, 15 hyperpigmentation, 11 photoaging, 12,14,17 and wounds. 13 Most included studies compared terpenoid-based therapy with vehicle control.…”
Section: Resultsmentioning
confidence: 99%
“…13 Most included studies compared terpenoid-based therapy with vehicle control. 6,[8][9][10][11][12][14][15][16][17] However, two studies compared terpenoid therapy with another non-phytochemical treatment modality, 7,13 and one study did not have a comparison group. 18 Ten studies reported that terpenoids were significantly more efficacious than vehicle control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadeghpour et al [36] ; Khazaei et al [41] ; Sabzghabaee et al [42] added that the potent estrogenic effect that is involved in phytoestrogens of fennel oil provide anti-inflammatory protective role by acting on estrogen receptors, reduce inflammatory response, suppress early apoptosis, cell death and fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Properties: Tonic and stimulant, decongestant, anesthetic and analgesic antipruritic, refreshing, antimicrobial, anti-inflammatory, expectorant, mucolytic, emmenagogue Kumar et al, 2011;Sabzghabaee et al, 2011;Singh et al, 2011).…”
Section: Peppermint Essential Oil (Mentha Piperita)mentioning
confidence: 99%